2019
DOI: 10.2147/ceor.s215069
|View full text |Cite
|
Sign up to set email alerts
|

<p>Budget Impact Of Including Avelumab As A Second-Line Treatment For Locally Advanced Or Metastatic Urothelial Cancer In The United States: Commercial And Medicare Payer Perspectives</p>

Abstract: ObjectiveTo estimate the budget impact of introducing avelumab as a second-line (2L) treatment option for patients with locally advanced or metastatic urothelial cancer (mUC) from the perspective of a US third-party payer (commercial and Medicare).MethodsA budget impact model (BIM) with a three-year time horizon was developed for avelumab. Efficacy and safety data were sourced from published literature and US package inserts. The analysis was conducted in collaboration with a specialist oncologist who validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Regarding the budget-holder perspective, one study calculated the budget impact from the hospital perspective (66), five adopted the health-plan perspective (45,46,48,55,64), and 16 adopted the third-party payer perspective including public health insurance, Medicare, and commercial insurance (42-44, 47-54, 56, 58, 59, 61, 65, 68). Five studies reported results from more than one perspective (43,50,54,58,68).…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the budget-holder perspective, one study calculated the budget impact from the hospital perspective (66), five adopted the health-plan perspective (45,46,48,55,64), and 16 adopted the third-party payer perspective including public health insurance, Medicare, and commercial insurance (42-44, 47-54, 56, 58, 59, 61, 65, 68). Five studies reported results from more than one perspective (43,50,54,58,68).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Of those, in five studies (14%), the authors took subsequent treatment costs based on guideline recommendations into account, while in the other six studies (24%), the authors took the subsequent treatment costs based on their own model structure and relative considerations into account. For example, Kongnakorn et al(50) calculated the costs of post-progression (on subsequent 3 line active treatment) and post-progression/off-treatment (best supportive care) as subsequent treatment costs, while Stellato et al (52) developed a Markov model and considered the costs of subsequent recurrence events in patients. Bly et al(54) andMistry et al (…”
mentioning
confidence: 99%
“…Avelumab has been studied and deemed that its use would have a cost-neutral impact within a US commercial and a Medicare health plan [ 87 ]. Based on that it is the lowest priced drug on the list ( Table 3 ), and the positive data from the phase III JAVELIN Bladder 100 trial, avelumab is a relatively affordable and a cost-effective option.…”
Section: Health Economic Factorsmentioning
confidence: 99%
“…Regarding the budget-holder perspective, one study calculated the budget impact from the hospital perspective (66), five adopted the health-plan perspective (45,46,48,55,64), and 16 adopted the third-party payer perspective including public health insurance, Medicare, and commercial insurance (42-44, 47-54, 56, 58, 59, 61, 65, 68). Five studies reported results from more than one perspective (43,50,54,58,68).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Of those, in five studies (14%), the authors took subsequent treatment costs based on guideline recommendations into account, while in the other six studies (24%), the authors took the subsequent treatment costs based on their own model structure and relative considerations into account. For example, Kongnakorn et al(50) calculated the costs of post-progression (on subsequent 3 line active treatment) and post-progression/off-treatment (best supportive care) as subsequent treatment costs, while Stellato et al (52) developed a Markov model and considered the costs of subsequent recurrence events in patients. Bly et al(54) andMistry et al (…”
mentioning
confidence: 99%